2021
DOI: 10.3390/molecules26226882
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B Attenuates Hepatic Stellate Cell Activation and Promotes Apoptosis to Protect against Liver Fibrosis

Abstract: The activation of hepatic stellate cells (HSC) plays a key role in the progression of hepatic fibrosis, it is essential to remove activated HSC through apoptosis to reverse hepatic fibrosis. Schisandrin B (Sch B) is the main chemical component of schisandrin lignan, and it has been reported to have good hepatoprotective effects. However, Schisandrin B on HSC apoptosis remains unclear. In our study, we stimulated the HSC-T6 and LX-2 cell lines with TGF-β1 to induce cell activation, and the proliferation and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…NASH with fibrosis is characterized by extensive accumulation of the extracellular matrix (ECM), which is usually followed by extensive tissue damage [57]. The fibrogenesis process in the liver is thought to mainly be regulated by hepatic stellate cells [58], and its activation produces collagen I (COL I), collagen III (COL III), and transforming growth factor-β (TGF-β) [4] in response to overexpression of X-box-binding protein 1 (XBP1) [59], NACHT, leucine-rich-repeat, pyrin domain-containing protein 3 (NLRP3) [60], and platelet-derived growth factor (PDGF) [57]. Collagen is the principal component of the extracellular matrix or scars.…”
Section: Fibrogenesis Pathwaymentioning
confidence: 99%
“…NASH with fibrosis is characterized by extensive accumulation of the extracellular matrix (ECM), which is usually followed by extensive tissue damage [57]. The fibrogenesis process in the liver is thought to mainly be regulated by hepatic stellate cells [58], and its activation produces collagen I (COL I), collagen III (COL III), and transforming growth factor-β (TGF-β) [4] in response to overexpression of X-box-binding protein 1 (XBP1) [59], NACHT, leucine-rich-repeat, pyrin domain-containing protein 3 (NLRP3) [60], and platelet-derived growth factor (PDGF) [57]. Collagen is the principal component of the extracellular matrix or scars.…”
Section: Fibrogenesis Pathwaymentioning
confidence: 99%
“…Li et al showed that Schisandrin B promotes HSC apoptosis against liver fibrosis. 56 Chiang et al reported that Lycium barbarum polysaccharide can attenuate hepatocyte apoptosis to suppress hepatic fibrosis. 57 These results are in keeping with our work.…”
Section: Discussionmentioning
confidence: 99%
“…Schisandrin B, salvianolic acid A, and kaempferol are active ingredients of FZHY that directly bind to PPARγ and inhibit the activity of HSCs 79 . Schisandrin B also showed a hepatoprotective effect by attenuating HSC activation and promoting apoptosis in vitro 28 . Furthermore, Schisandrin B controls macrophage polarization by activating PPARγ 80 .…”
Section: Mechanism Of Tcm In the Treatment Of Hepatic Fibrosis By Act...mentioning
confidence: 99%